(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
In higher education, feedback serves not only as an evaluation tool but also as a means to support active student engagement in the learning process. However, feedback practices are often one-way, leaving students as passive recipients. This study aims to explore how reflective dialogic assessment is constructed through teacher-student feedback journals and how these practices support reflective learning in a postgraduate English Language Teaching (ELT) program. The study used a qualitative approach with a narrative inquiry design involving postgraduate students in the Academic Writing course. Data were obtained through teacher-student feedback journals, written reflections, and student responses to lecturer feedback, which were then analyzed thematically and narratively. The results showed that dialogic feedback encouraged students to be more reflective, recognize their academic weaknesses, and be more active in revising their writing. The two-way interaction through feedback journals also deepened students’ understanding of the academic writing process. These findings suggest that teacher-student feedback journals have the potential to support more reflective, dialogic, and student-centered learning in the postgraduate ELT context.